The Value of Direct Immunofluorescence on Proteinase-Digested Formalin-Fixed Paraffin-Embedded Skin Biopsies. (February 2018) - Valencia-Guerrero, Aida; Deng, April; Dresser, Karen; Bouliane, Gail; Cornejo, Kristine M.
Abstract : Abstract: Direct immunofluorescence (DIF) on frozen tissue (DIF-F) is the method of choice for the identification of immune deposits present in skin and other tissues. DIF can also be performed on formalin-fixed paraffin-embedded tissue (DIF-P) after antigen retrieval with proteases and has proven to be of value in renal pathology. However, its utility in skin biopsies has not been fully examined. In this study, we performed DIF-P on 60 skin biopsies that comprised of bullous pemphigoid (n = 18), pemphigoid gestationis (n = 1), pemphigus (n = 7), linear IgA disease (n = 7), vasculitis (n = 20), lupus erythematosus (n = 3), and dermatitis herpetiformis (n = 4) cases. We compared the results of DIF-P with those of DIF-F from the same patients. The diagnostic features were found in 15 of 19 (79%) pemphigoid (bullous pemphigoid and pemphigoid gestationis), 3 of 7 (43%) pemphigus, 3 of 7 (43%) linear IgA disease, 14 of 20 (70%) vasculitis, 1 of 3 (33%) lupus erythematosus, and none (0%) of the dermatitis herpetiformis cases tested. Overall, DIF-P is less sensitive than DIF-F but seems to be a valuable technique that could aid in the diagnosis of vasculitides, immunobullous, and connective tissue disorders when fresh tissue is unavailable.